2017
DOI: 10.1038/ncomms13854
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac afferent activity modulates the expression of racial stereotypes

Abstract: Negative racial stereotypes tend to associate Black people with threat. This often leads to the misidentification of harmless objects as weapons held by a Black individual. Yet, little is known about how bodily states impact the expression of racial stereotyping. By tapping into the phasic activation of arterial baroreceptors, known to be associated with changes in the neural processing of fearful stimuli, we show activation of race-threat stereotypes synchronized with the cardiovascular cycle. Across two esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 55 publications
(109 reference statements)
13
106
2
1
Order By: Relevance
“…We studied the association between the cardiac cycle and self-paced visual sampling as well as visual recognition memory for pictures of different emotional valence. We hypothesized that facilitated visual processing (Pramme et al, 2014(Pramme et al, , 2016)-observed specifically for relevant or emotionally salient stimuli (Azevedo et al, 2018(Azevedo et al, , 2017Garfinkel et al, 2014)-as well as facilitated oculomotor processing during systole (Ohl et al, 2016) guides active perception in the shape of a preference to prompt a relevant visual stimulus during early phases of the cardiac cycle. We observed a significant accumulation of key presses (i.e., prompted picture onsets) during systole, thereby showing for the first time a coupling between self-paced visual sampling and the heartbeat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the association between the cardiac cycle and self-paced visual sampling as well as visual recognition memory for pictures of different emotional valence. We hypothesized that facilitated visual processing (Pramme et al, 2014(Pramme et al, , 2016)-observed specifically for relevant or emotionally salient stimuli (Azevedo et al, 2018(Azevedo et al, , 2017Garfinkel et al, 2014)-as well as facilitated oculomotor processing during systole (Ohl et al, 2016) guides active perception in the shape of a preference to prompt a relevant visual stimulus during early phases of the cardiac cycle. We observed a significant accumulation of key presses (i.e., prompted picture onsets) during systole, thereby showing for the first time a coupling between self-paced visual sampling and the heartbeat.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate perception and action within a comprehensive framework of mind-brain-body interactions, we studied cardiac-related sensorimotor processing in a self-paced visual sampling paradigm, in which participants decide when to press a key to see a task-relevant visual stimulus. Extending studies that emphasize a selectivity of this effect for motivationally salient, passively presented stimuli (Azevedo et al, 2018(Azevedo et al, , 2017Garfinkel et al, 2014), we predicted that observers implicitly act upon a relevant visual stimulus such that it is received (and perceived) during preferred cardiac phases. More specifically, we hypothesized that visual sampling would be biased toward processing taskrelevant pictures during systole.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Illustrations of this interoceptive dimension are found, for example, in cardiac timing experiments where afferent heartbeat signals affect decisions, emotional processing, and memory. [14][15][16] Three "psychological" dimensions refer more directly to the perception of interoceptive signals: interoceptive accuracy, sensibility, and awareness. 10 These dimensions developed from the use of tests of interoceptive sensitivity/ability, such as heartbeatdetection tasks.…”
Section: Dimensions Of Interoceptionmentioning
confidence: 99%
“…122 Research is currently investigating the nature of interoceptive deficits associated with ASCs. Work in children is divergent, with one study suggesting that interoceptive accuracy is intact in autis-tic children and adolescents (aged [8][9][10][11][12][13][14][15][16][17], 123 while a subsequent study found that interoceptive accuracy, ascertained using heartbeat tracking, was markedly impaired in a comparable child and adolescent autistic sample. 52 Impaired interoceptive accuracy has also been shown in autistic adults, demonstrated using the heart beat tracking task, where significantly lower interoceptive accuracy scores were observed relative to a matched control group.…”
Section: Autism Spectrum Conditionsmentioning
confidence: 99%